The Influence of Green Products and Green Advertising on Purchasing Decisions (Study on Honda Beat Motorcycle Buyers with ESP Features in Medan Area District) - Felix; Hommy Dorthy Ellyany Sinaga (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
Motorcycles are a means of transportation that has been known to consumers for a long time from year to year until now it has experienced rapid development. The purpose of this study is to analyze The Influence of Green Product and Green Advertising on Purchasing Decisions of Honda Beat Motorcycle Buyers with ESP Features in Medan Area District. This type of research uses quantitative research, data collection techniques using questionnaires and samples in this study amounted to 80 samples. The results of the study concluded that partially Green Product has a positive and significant influence on purchasing decisions and Green Advertising has a positive and significant influence on purchasing decisions. Simultaneously Green Product and Green Advertising have a positive and significant influence on purchasing decisions